Challenges confronting construction project management system for sustainable construction in developing countries: professionals perspectives (a case study of Nigeria) - Ogunde, A.O.; Olaolu, O.; Afolabi, A.; Owolabi, J.; Ojelabi, R. (Penerbit Universiti Kebangsaan Malaysia, 2017)
The success of the Nigerian construction industry can be aligned with the use of construction project management systems, although, the industry has been maligned by issues such as building collapse, incessant delays, abandonment and cost overrun. It is therefore imperative to examine the challenges confronting construction project management system in Nigeria. In this study the descriptive survey method was adopted and data were obtained by means of inquiries using questionnaires. A sample size of fifty nine (59) construction professionals was used for the study. The study reveals that location of a project majorly influences Project Manager’s decision making on project planning. It asserted the crucial importance of Management skills required in practicing construction project management. In conclusion, the result identified that passive participation from Project Manager, lack of client involvement in making decisions, provision of substandard materials, design error, lack of effective communication and poor treatment of workforce are challenges hampering the use of construction project management. The study recommends the institutionalization of construction project management practice, compulsion of adequate training and skill modification programs for construction professionals to aid the sustainability of construction project management systems in Nigeria.